Cerebrospinal Fluid Protein Concentrations in Hydrocephalus - Florian Wilhelmy; Matthias Krause; Stefan Schob; Andreas Merkenschlager; Robin Wachowiak; Wolfgang Härtig; Jürgen Meixensberger; Janina Gburek-Augustat; Tim Wende (MDPI AG, 2023)
CSF protein levels are altered in neurological disorders, such as hydrocephalus of different etiologies. In this retrospective observational study, we analyzed cerebrospinal fluid (CSF) samples in hydrocephalic diseases such as aqueductal stenosis (AQS, n = 27), normal pressure hydrocephalus (NPH, n = 24), hydrocephalus communicans (commHC, n = 25) and idiopathic intracranial hypertension (IIH)/pseudotumor cerebri (PC, n = 7) in comparison with neurological patients without hydrocephalic configuration (control, n = 95). CSF was obtained through CSF diversion procedures and lumbar punction and analyzed for protein concentrations according to the institution's laboratory standards. We found significantly decreased CSF protein levels in patients suffering from AQS (0.13 mg/dL [0.1-0.16 mg/dL] p = 2.28 × 10−8) and from PC (0.18 mg/dL [0.12-0.24 mg/dL] p = 0.01) compared with controls (0.34 mg/dL [0.33-0.35 mg/dL]). Protein levels were not altered in patients suffering from commHC and NPH compared with neurologically healthy individuals. We propose that a decrease in CSF protein levels is part of an active counterregulatory mechanism to lower CSF volume and, subsequently, intracranial pressure in specific diseases. Research regarding said mechanism and more specific proteomic research on a cellular level must still be performed to prove this hypothesis. Differences in protein levels between different diseases point to different etiologies and mechanisms in different hydrocephalic pathologies.